Study of scattering from turbulence structure generated by propeller with FLUENT. Issue 3 (3rd July 2017) - Luo, Gen
Abstract: In this article, the turbulence structure generated by a propeller is simulated with the computational fluid dynamics (CFD) software FLUENT. With the method of moments, the backscattering radar cross sections (RCS) of the turbulence structure are calculated. The scattering results can reflect the turbulent intensity of the wave profiles. For the wake turbulence with low rotating speed, the scattering intensity of HH polarization is much smaller than VV polarization at large incident angles. When the turbulence becomes stronger with high rotating speed, the scattering intensity of HH polarization also becomes stronger at large incident angles, which is almost the same with VV polarization. And also, the bistatic scattering of the turbulence structure has the similar situation. These scattering results indicate that the turbulence structure can also give rise to an anomaly compared with traditional sea surface. The study of electromagnetic (EM) scattering from turbulence structure generated by the propeller can help in better understanding of the scattering from different kinds of waves and provide more bases to explain the anomalies of EM scattering from sea surfaces.